Student Preferences on Using Artificial Intelligence (AI) Platform in Language Learning - Roswani Siregar; Heni Subagiharti; Diah Syafitri Handayani; Sutarno Sutarno; Ahmad Laut Hasibuan; Efendi Barus (International Journal of Educational Research Excellence (IJERE), 2024)
Artificial Intelligence (AI) is a system that is developed and continues to innovate in various fields with the aim of making human work easier. As the name suggests, artificial intelligence is made to resemble human intelligence and is applied in various fields. Currently Artificial Intelligence technology is also used in the field of education, including teaching foreign languages. This article, which is based on a short field study, aims to find out student references regarding the use of Artificial Intelligence. The use of artificial intelligence (AI) in English Language Teaching (ELT) can be seen as both a benefit and a potential threat, depending on how it is used and implemented. On the one hand, AI technology has the potential to make language learning more efficient and effective, by providing personalized feedback and practice exercises tailored to the different student’s needs and learning styles. The research method used to determine this phenomenon is a qualitative descriptive research method with questionnaire data collection techniques by asking questions that can be answered directly by respondents according to their respective answers. Artificial Intelligence (AI) has the potential to play an important role in helping students in various tasks in learning English, i.e finding out the the meaning and definition of words, translating sentences, improving grammar, etc with reliable and timely results. However, on the other hand, AI has an impact on student abilities. Students are increasingly dependent on AI assistance in learning, thereby reducing its role in critical thinking and using memory